Perilaku seksual pranikah siswa di sman 2 praya lombok tengah ntb: Premartial sexual behavior of students of sman 2 praya central lombok, ntb - Teguh achmalona; Pa’ni, D. Mustamu Qamal; Sutomo, Suswinda Yuli; Usman, Arip (Bali Medika Jurnal, 2021)
Premarital sexual behavior is a symptom or behavior that is driven by sexual desire towards the opposite sex which leads to sexual relations without a legitimate bond. In Indonesia around 62.7% of teenagers have had sex outside of marriage. 20% of 94,270 women who experience pregnancy outside of marriage also come from adolescents and 21% of them have had an abortion. The purpose of this study is to explore more in depth information regarding premarital sexual behavior of students in SMAN 2 Praya, Central Lombok Regency, NTB province. This research was conducted at SMAN 2 Praya, Central Lombok Regency, March-April 2020. The method used was qualitative through in-depth interviews and FGD (Focus Group Discusion). Determination of informants by choosing informants intentionally in accordance with the research objectives, namely informants who have premarital sexual experience.The technique of checking the validity of the data using the triangulation method. The results of the research presented by the informants included lack of knowledge of students and parents about reproductive health, students 'and parents' perceptions of wrong premarital sexual behavior, the role of parents who were lacking in preventing premarital sexual behavior, neighborhoods and local habits that support , media abuse by students to get pornographic content. According to informants there is no school PIKR to provide health education related to positive sexual behavior and reproductive health. It is expected that the relevant schools and offices are more optimal in conducting health promotion especially health promotion on premarital sexual behavior and reproductive health through the ICR program in order to instill a strong foundation of positive sexual behavior so as to prevent the emergence of negative sexual behavior.